Designing Medan Coffee Center with a Contemporary Architecture Approach - Ghaisani, Iwana; Hadinugroho , Dwi Lindarto (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Medan Coffee Center is a building that includes everything related to coffee, where coffee lovers can easily get various items related to coffee such as coffee tools, various types of coffee beans and powder, as well as various supporting tools in making coffee, besides that the coffee community can have a place that can be a place for them to develop various potentials in exploring various kinds of coffee. Medan City itself does not yet have a special area to accommodate everything related to this coffee. Therefore, it is necessary to establish an area that can encourage young people to develop their interests and creativity and become a new educational tourism area in Medan City. It is expected that the rooms in the Medan Coffee Center building play an important role as a public facility that has social value in understand local coffee culture, can become a new tourist destination, and provide educational services on various matters related to coffee. As a result, this building has a contemporary building style thanks to the contemporary architectural style and modern local character and is expected to be one of the drivers and realizations of a dynamic Medan City for both the younger and older generations